Pengaruh Latar Belakang Pendidikan Orangtua Terhadap Kedisiplinan Anak - Muhamad Al’vizar; Diena San Fauziya (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Parents' attention in educating children in the family environment is very important because the family is the best place to start education, in the family environment learning opportunities can be utilized to develop children's talents. Discipline is obedience and obedience to something that has been agreed upon. Discipline can be trained from an early age through the family's parenting style, in which parents play a bigger role. The method used in this research is a descriptive analysis research method. The research results show that every person who has a different educational background certainly wants their child to be successful and disciplined in the future, therefore every parent provides rules, motivation and encouragement to become an educated and disciplined person because that is important.